New pharmacological therapies for COPD - Barnes, Peter (Henry Stewart Talks, 2012)
New treatments for COPD include long-acting bronchodilators and combinations, Mediator antagonists, including chemokine antagonists, Broad-spectrum anti-inflammatory treatments, Reversal of corticosteroid resistance by increasing HDAC2